THE COMBINATION OF GREEN BEANS AND CORN AMYLUM AS A TABLET DESTROYING MATERIAL - Abdul Rahim (Universitas Islam Negeri Alauddin Makassar, 2020)
Mung beans (Phaseolus radiatus L.) and maize (Zea mays L.) are quite a lot of food crops in Indonesia. The area of mung bean plantations in 2008 reached 276,892.00 Ha with the amount of green bean production in the third place. Meanwhile, maize is a food plant that is easily available because it is cultivated in the tropics and is not a deficient crop. Starch is often used in the manufacture of tablets as an additional material, one of which is a disintegration. Research on the combination of starch from corn and starch from green beans has never been carried out. We know it that green beans and corn contain 80% starch if they have been dried or powdered. Starch from green beans and maize when developed and processed will overcome dependence on imported starch. This study aims to test the combination of green bean starch and corn starch to get a good crushing material. It carried the procedure of this research out by making a comparison formula for the crushing material of mung bean starch and corn, namely 1: 0, 1: 1 and 0: 1. Starch making, granule making, granule evaluation, tablet making, and tablet physical test. This research is experimental. Data analysis was carried out theoretically, comparing with literature and statistical analysis using One Way ANOVA method with 95% confidence. The results showed that paracetamol tablets with the ingredients of crushing mung bean starch, green bean starch: corn starch, and corn starch met the requirements for the physical properties of the tablets. The disintegration time of paracetamol tablets with the ingredients of crushing green bean starch, green bean starch: corn starch, and corn starch was 3.05 minutes, 11.1 minutes and 9.42 minutes.